EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DAN LT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMP (Jurnal Pendidikan Madrasah, 2016)
The objective of this research is to know the effectivity of cooperative learning method with Team Games Tournament (TGT) type and Learning Tournament (LT) compared with conventional learning for ability in mathematics problem-solving. The type of this research is pseudo experiment with nonequivalent control group design. Independent variable, which is TGT and LT learning method, and dependent variable, which is capacity in mathematics problem-solving were variables covered in this research. The subject of the research consisted of population of 7th grade students of SMP Negeri 1 Ngemplak and samples were students of class VII A, VII B, and VII C. Pretest and posttest on capacity in mathematics problem-solving were used as the instruments. Data analysis techinque used in this research is Kruskal-Wallis test by using software SPSS 15.0 The result of this research showed that: First, TGT learning method was more effective than conventional learning method for ability in mathematics problem-solving; Second, LT learning method was not more effective than conventional learning method for ability in mathematics problem-solving; Third, TGT learning method was more effective than LT learning method for ability in mathematics problem-solving.